Founder Effect of KHDC3L, p.M1V Mutation, on Iranian Patients with Recurrent Hydatidiform Moles - Fallahi, Jafar; Anvar, Zahra; Razban, Vahid; Momtahan, Mozhdeh; Namavar-Jahromi, Bahia; Fardaei, Majid (Iranian journal of medical sciences, 2020)
Recurrent hydatidiform moles (RHMs) are an unusual pregnancy with at least two molar gestations that are associated with abnormal proliferation of trophoblastic tissue and a failure in the embryonic tissues development. Three maternal-effect genes, including and have been identified as the cause of RHMs. The present study aimed to understand the association of a founder mutation with the incidence and prevalence of a disease in different individuals of a population. 14 unrelated Iranian patients with recurrent reproductive wastage, including at least two HMs, entered this study. In order to find a possible mutation in , all the 14 samples were Sanger sequenced. For haplotype analysis, three single nucleotide polymorphisms (SNPs) were selected with highest Minor Allele Frequency along . A common mutation with the same haplotype was identified in four out of 14 patients with RHM. Regarding the present study, c.1A>G is the highest reported mutation in KHDC3L so far and is also the first report of the homozygous state that has led to RHM. c.1A>G mutation in is the highest reported mutation around the world. Our data also demonstrated the presence of founder effects for this particular mutation in Iranian populations. These data suggest that the high frequency of this mutation is potentially responsible for a higher rate of RHM in Iran.